2012
DOI: 10.1364/oe.20.022649
|View full text |Cite
|
Sign up to set email alerts
|

A new design of light illumination scheme for deep tissue photoacoustic imaging

Abstract: Abstract:A new light illumination scheme to increase imaging depth in photoacoustic (PA) imaging was designed and evaluated by in silico simulations and tested by in vitro experiments. A relatively large portion of the light energy shining into the body of a human reflects off the skin surfaces. Collecting the reflected light and redirecting it onto skin surfaces will increase the effective input energy, resulting in an increase of light penetration depth for the same light source. Its performance in PA imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
2
30
0
1
Order By: Relevance
“…A significant difference with p < 0.05 using t-test was shown for both cases. PA signal enhancement in two different wavelengths of 689 and 800 nm are in good agreement with laser fluence increase shown above and our previous in silico and in vitro results [4], [9]. This experiment result implies that PA signal would be amplified by increased laser fluence at depth when using the light catcher.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…A significant difference with p < 0.05 using t-test was shown for both cases. PA signal enhancement in two different wavelengths of 689 and 800 nm are in good agreement with laser fluence increase shown above and our previous in silico and in vitro results [4], [9]. This experiment result implies that PA signal would be amplified by increased laser fluence at depth when using the light catcher.…”
Section: Resultssupporting
confidence: 91%
“…They successfully demonstrated a concentrated beam profile with enhanced laser photon density using their probe. Zhaohui et al [4] suggested a new light illumination scheme for deep tissue PA imaging and the proof of concept was shown through a finite-element simulation. The proposed scheme was based on a fact that light energy is considerably lost by reflection at the skin surface depending on the incident angle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AE ultrasound detectors could also operate as ultrasound receivers for photoacoustic imaging [27], where the acoustic signals are generated by the absorption of a high-energy laser pulse. The potentially low cost, high bandwidth, and robustness of AE hydrophones make them particularly attractive for many biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…[2] At 800nm wavelength of induced light, about 22~29% of the light is reflected with incidence angle 20˚. [3,5] Light reflectance increases as the thickness of the skin increases as well. Approximately 13% (19% to 32%) reflectance increases at 800nm with 1.17mm (0.43mm to 1.6mm) skin increases.…”
Section: Introductionmentioning
confidence: 99%